2018
DOI: 10.33665/ijear.2018.v05i02.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a compact ionosphere disturbance over the earthquake: A Focus on Schumann resonance

Abstract: We model perturbations of vertical electric and horizontal magnetic fields of Schumann resonance by a localized seismogenic non-uniformity in the Earth-ionosphere cavity with simultaneous accounting for the day-night non-uniformity. The source and receiver are placed at the same meridian and the latitudes covering 22.5° N and 22.5° S. The propagation path is positioned at the night (60° E) or the dayside (120° E) of morning terminator. The localized nonuniformity moves either along or across the propagation pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Still, these reflect both qualitative and quantitative features observed experimentally. These already published data show that seismogenic modifications in the SR spectra might be successfully explained by radio wave reflection from the atmospheric nonuniformity above the EQ position (Galuk et al, 2019; Nickolaenko et al, 2018a, 2018b; Nickolaenko & Hayakawa, 2013; Nickolaenko et al, 2006). The conductivity modifications of this kind are able to influence only ELF radio waves.…”
Section: Introductionmentioning
confidence: 92%
“…Still, these reflect both qualitative and quantitative features observed experimentally. These already published data show that seismogenic modifications in the SR spectra might be successfully explained by radio wave reflection from the atmospheric nonuniformity above the EQ position (Galuk et al, 2019; Nickolaenko et al, 2018a, 2018b; Nickolaenko & Hayakawa, 2013; Nickolaenko et al, 2006). The conductivity modifications of this kind are able to influence only ELF radio waves.…”
Section: Introductionmentioning
confidence: 92%
“…The main source of the Schumann resonances is lightning activity, occurring in the tropical belt around the world, creating electromagnetic waves that propagate within the cavity [38][39][40]. For extensive details on the subject of SR, the reader may refer to the books by Nickolaenko and Hayakawa [41,42] and relevant articles [43][44][45][46][47][48][49][50] where the theory of SR physics, applications, and technical details about data recording were analyzed in detail.…”
Section: The Involvement Of Elf Waves In Earth Sciencesmentioning
confidence: 99%
“…S. S. et al [103] studied the changes in SR signals 15 and 5 days before and after earthquake events, and concluded that SR anomalies appeared several hours earlier than ionospheric anomalies. A. P. Nickolaenko, M. Hayakawa et al [104][105][106] used ELF observation data from Nakatsugawa and Moshiri stations in Japan to report significant SR anomalies before and after multiple earthquakes and found that the estimated arrival angle of the abnormal signal was consistent with the azimuth angle from the station to the epicenter, proving that seismic electromagnetic radiation is the main cause of SR anomalies. Christofilakis et al [107] used the close ELF observation records obtained during the earthquake duration (the ground observation station is only 365 km from the epicenter) to detect the extreme electromagnetic events before and after the occurrence of seismicity and summarized the laws of these extreme electromagnetic events.…”
Section: The Correlation Of Anomalies In Schumann Resonances and Eart...mentioning
confidence: 99%